SWOT Analysis of Indonesian Coastal Tourism Destination Marketing in the International Office - Hanif, Sayed Muhammad; Widodo, Slamet (Sinergi International Journal of Economics, 2024)
This study examines the marketing strategy of beach tourism destinations in Indonesia through a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis approach. The background of this study is based on the importance of beach tourism as a major economic sector that contributes significantly to national income, especially in countries with great beach tourism potential such as Indonesia. The research method used is a SWOT analysis to identify the strengths, weaknesses, opportunities, and threats faced by beach tourism destinations in Indonesia. The results of the study show that the main strengths of Indonesian beach tourism destinations include pristine natural beauty, rich underwater ecosystems, supporting facilities, and rich local culture. However, weaknesses such as lack of infrastructure, ineffective promotion, and low service quality are still major challenges. Opportunities include increasing global interest in Indonesian beach tourism, advances in information technology, and sustainable tourism trends. Meanwhile, threats such as intense global competition, natural disasters, and marine pollution require mature risk management. The conclusion of this study emphasizes the need for innovative and sustainable marketing strategies to improve the global competitiveness of Indonesian beach tourism. Practical recommendations include improving infrastructure, more effective promotion, and developing sustainable tourism.